Subori pine cenoses herbaceous ground cover biodiversity of the Voronezh Region - Popova Valentina; Popova Anna; Tseplyaev Aleksey (BIO Web of Conferences)
An assessment of the biodiversity and abundance of the herbaceous ground cover of the subori pine cenoses in the Voronezh Region was carried out in the long term (1990 to 2023) under the influence of the factor of reducing forest areas and identifying the most resistant species. Over the observation period from 1990 to 2020, the species composition of the vegetation cover of the subori changed insignificantly. By 2020, plants of the Red Book of the Voronezh Region, wintergreen, feather grass, as well as subori plants (sweet grass, round-leaved bellflower, nettle-leaved bellflower), had disappeared. The species composition of subori was replenished with meadow and ruderal plants, as well as dry pine forest plants, the abundance of individual species of cereals or liliaceae increased, the abundance of labiates, legumes and polypods decreased. Based on the ecological-cenotic analysis and the abundance of species, 26 species (out of 54) were identified that belong to mesophytes and xerophytes.